ANALYSIS OF FIBER-REINFORCED ELEMENTS FROM COMPOSITE MATERIALS - Bogdan, Svitlana; Bogdan, Dmytro (Problems of Friction and Wear, 2025)
The limit state of two polymer layered composite elements was studied using a numerical-analytical method, employing the finite element method during their deformation, damage, and failure. Stress intensity factors for normal separation were determined for developed complex-shaped models with initial imperfections in the form of cracks, simulating defects in the composite structure. A comparative analysis of the obtained calculated values of critical load with the experimental studies and adaptation of the developed methodology were conducted.